2007
DOI: 10.1007/s10658-007-9178-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Plasmopara angustiterminalis isolate from Xanthium strumarium

Abstract: Leaves of Xanthium strumarium infected with downy mildew were collected in the vicinity of a sunflower field in southern Hungary in 2003. Based on phenotypic characteristics of sporangiophores, sporangia and oospores as well as host preference the pathogen was classified as Plasmopara angustiterminalis. Additional phenotypic characters were investigated such as the size of sporangia, the number of zoospores per sporangium and the time-course of their release. Infection studies revealed infectivity of the P. an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Although the B. tulasnei specimens from Senecio vulgaris formed a distinct lineage within the plurivorous clade 1 with weak bootstrap support in ME and MP, and strong support in ML and BA, an extended sampling of specimens, multigene analyses, and cross-infection tests might be necessary for clarifying whether they are distinct from the other Bremia accessions contained clade 1. However, increased sampling and multigene analyses are preferable over cross-inoculation experiments, as for example Komjáti et al (2007) reported that Plasmopara angustiterminalis can infect some sunflower lines, albeit the pathogen is highly distinct from P. halstedii based on both morphological (Novotel'nova 1963) and molecular phylogenetic data , Komjáti et al 2007). For the Bremia clade 3, exclusively found on Cirsium, it is noteworthy that accessions from Cirsium arvense and Cirsium oleraceum are separated with weak support in ME and MP, moderate support in ML and high support in BA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the B. tulasnei specimens from Senecio vulgaris formed a distinct lineage within the plurivorous clade 1 with weak bootstrap support in ME and MP, and strong support in ML and BA, an extended sampling of specimens, multigene analyses, and cross-infection tests might be necessary for clarifying whether they are distinct from the other Bremia accessions contained clade 1. However, increased sampling and multigene analyses are preferable over cross-inoculation experiments, as for example Komjáti et al (2007) reported that Plasmopara angustiterminalis can infect some sunflower lines, albeit the pathogen is highly distinct from P. halstedii based on both morphological (Novotel'nova 1963) and molecular phylogenetic data , Komjáti et al 2007). For the Bremia clade 3, exclusively found on Cirsium, it is noteworthy that accessions from Cirsium arvense and Cirsium oleraceum are separated with weak support in ME and MP, moderate support in ML and high support in BA.…”
Section: Discussionmentioning
confidence: 99%
“…For the Bremia clade 3, exclusively found on Cirsium, it is noteworthy that accessions from Cirsium arvense and Cirsium oleraceum are separated with weak support in ME and MP, moderate support in ML and high support in BA. This could indicate some degree of host specialisation and genetic diversification on the various Cirsium species, which should be investigated by a more intense sampling of this group and by including additional genes with high phylogenetic resolution, like ITS (Choi et al 2007a;Thines 2007). Considering the results of Voglmayr et al (2004), it is likely that extended sampling from other hosts, investigated with highly variable genes, will reveal additional phylogenetically distinct lineages that should be considered independent species.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility that two potential pathogen species may infect the same host species cannot be the sole criterion for species rejection, as for both Hyaloperonospora (Göker et al 2009) and Plasmopara (Komjáti et al 2007) it is known that phylogenetically clearly distinct species are able to infect the same host species.…”
Section: A -Length Ofmentioning
confidence: 99%
“…Narrow species concepts such as those found in Novotelnova scorzonerae, Paraperonospora leptosperma, Plasmopara angustiterminalis or Plasmopara on Flaveria bidentis are supported by the new characters analysed (Spring et al 2003;Thines 2006;Komjati et al 2007;Voglmayr and Constantinescu 2008). In this context, recent studies on downy mildew of Xanthium strumarium (Komjáti et al 2007) in Hungary and on a naturalized population of the perennial sunflower hybrid Helianthus x laetiflorus (Spring et al 2003) revealed that the former is correctly classified as P. angustiterminalis Novotelnova while the latter was indistinct from downy mildew samples collected from annual oilseed sunflower. The fact that both isolates readily infected H. annuus seedlings when sporangia were used as inoculum is questioning Novotelnova's (1966) concept of differentiating specific forms of P. helianthi according to infection patterns on annual or perennial sunflower species.…”
Section: Introductionmentioning
confidence: 88%